Pushing Piezoelectric Transmitters to the MHz Regime - Tristan A. Wilson; Srinivas Prasad Mysore Nagaraja; Stewart Sherrit; Devin Willey; Adam Wildanger; Darmindra D. Arumugam (IEEE Open Journal of Antennas and Propagation)
Transmitters driven by piezoelectric resonators have been shown to radiate quasistatic electromagnetic waves in the low frequency and very low frequency (LF and VLF) bands. These devices make use of the inverse piezoelectric effect to convert continuous-wave excitation into mechanical stress and strain that is oscillatory in nature. This leads to the generation of electrical charge that accelerates onto floating electrodes exploiting topological symmetry, which results in dipole-like field radiation. The radiation efficiency can be three orders of magnitude greater than that of conventional electrically-small antennas operating in this frequency range. To our knowledge, this is the first time that radiation has been shown with lithium niobate (LiNbO3) acoustically-driven transmitters operating in the MHz regime. The measured results from a line-of-sight spatial power drop-off experiment show great promise for physically realizable transmitters much smaller than the current state-of-the-art at these frequencies. These devices offer great potential to be used as compact low-power transmitters on platforms constrained by power and volume, such as drones, quadcopters, and microsatellites. It is suggested that arraying these devices may allow for much more compact spacecraft radar and communication hardware, which can greatly benefit the overall system performance.